2022
DOI: 10.3389/fpubh.2022.852683
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Residents' Subjective Class Identity and Physical Activity Participation Mechanism

Abstract: The aim of the present study was to evaluate the association between participation in physical activity and subjective class identity of people in urban and rural areas of China. The effect of social class identity on residents' physical activity was tested using the Monte Carlo method. There is a positive correlation between physical activity and the subjective class identity of urban and rural residents (r = 0.351, p < 0.01). It has been also seen that subjective class identity can significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In the data of CGSS 2017, there were problems related to this variable. The question is “A30” ( Yang et al, 2022 ). In the past year, do you often engage in the following activities in your spare time?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the data of CGSS 2017, there were problems related to this variable. The question is “A30” ( Yang et al, 2022 ). In the past year, do you often engage in the following activities in your spare time?…”
Section: Methodsmentioning
confidence: 99%
“…First, the reliability and validity of the data were tested by Stata 16.0 ( Table 2 ). Similar methods are often used in computational sociology ( Jin and Vai, 2014 ; Jin et al, 2020 ; Li and Liu, 2021 ; Yang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are almost no gender differences in adolescents' self-rated health in cities, while in rural areas, male adolescents have better self-rated health than female adolescents, which also reflects that the living conditions of female adolescents in rural areas are relatively poor, which is related to the concept of men being superior to women in rural areas of China; that is, in rural areas of China, women often undertake housework from an early age. At the same time, the idea of son preference makes women in rural areas more likely to choose to watch TV and other activities at home ( 10 , 14 ). It was found that the self-assessment activities of adolescents in rural areas can promote their physical health.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some studies believe that physical activity can increase people's subjective identity, and the improvement of subjective identity requires a certain income base. Families with higher income will improve their health level through their economic capital ( 10 ). This is because family income, as a type of social capital, can affect teenagers' physical and mental health through a variety of ways or channels.…”
Section: Introductionmentioning
confidence: 99%
“…China's urban-rural dual system structure and degree of marketization lead to sound urban sports facilities, and the per capita share is greater than that of rural areas. There are obvious differences in mass sports participation between urban and rural areas (6). Considering that urban factors may cause an increase or decrease in the sports population, this paper directly uses Urban = 1, and rural = 2 as the measurement index, so residence is included in the independent variable index.…”
Section: Independent Variable: Town + Social Status + Offspringmentioning
confidence: 99%